Studi Kasus Implementasi Teknologi Chatbot sebagai Asisten Virtual dalam Menjawab Pertanyaan Mahasiswa di Lingkungan Kampus - Damayanti, Desy; Nuzuli, Ahmad Khairul (LPPM Institut Nasional Laa Roiba Bogor, 2024)
ABSTRACT. This research investigates the implementation of chatbot technology as a virtual assistant in the campus environment to answer students' questions. A case study was conducted at a large university with a significant number of students. The research method used was field research with a qualitative approach. Data was collected through interviews with campus information system administrators and several students who used the chatbot. Data was also collected from chatbot conversation logs. The results of the research show that the implementation of chatbot technology has a positive impact on students. The chatbot is able to provide quick and accurate answers to routine questions such as class schedules, classroom locations, and other academic information. The availability of the chatbot service 24/7 is well-received by students as it allows them to obtain information without waiting for office hours. However, there are some challenges in implementing this chatbot. The main issue is related to natural language understanding, especially for complex or ambiguous questions. Students prefer to talk to administrative staff in certain situations that require more detailed explanations. This research provides a significant contribution to understanding the implementation of chatbots as virtual assistants in higher education. Further efforts are needed to improve the artificial intelligence of the chatbot to respond to questions more effectively. In facing challenges and potentials, universities and other educational institutions can use these findings as a guide to optimize the use of chatbots and enhance students' services and experiences in the future. By continuously improving and developing chatbot technology, it is hoped to further enhance the efficiency and accessibility of information for students in the campus environment. Keywords: Chatbot, Virtual Assistant, Students